HUBUNGAN SELF CONSCIOUSNESS DENGAN KUALITAS HIDUP REMAJA YANG MENGALAMI JERAWAT DI DESA KALI SELATAN KECAMATAN PINELENG - Belinda T. Undap; Maria J. Wantah; Gloridei L. Kapahang (PSIKOPEDIA, 2022)
This study aims to determine the relationship between self-consciousness and quality of life in adolescents who experience acne in Kali Selatan village, Pineleng sub-district. This research uses quantitative methods. The subjects in this study were 48 adolescents who experienced acne in Kali Selatan village, Pineleng sub-district, using a saturated sample using a sampling technique. The research instrument is the WHOQOL-BREF (2004) scale and the self-consciousness scale (SCS-R) adapted from Scheier & Carver (2003) which has been modified by researchers. Test the hypothesis using the Pearson correlation. The results of the hypothesis test showed the pattern of relationship between self-consciousness and quality of life is significant. This shows that the H1 hypothesis is accepted. The H1 hypothesis is that there is a relationship between self-consciousness and the quality of life of adolescents who experience acne in Kali Selatan Village, Pineleng District.